Infrared and Raman Investigation of Supported Phosphotungstic Wells- Dawson Heteropolyacid - Bonivardi, Adrian Lionel (2014)
The combination of both infrared and Raman spectroscopy are powerful tools to obtain information of catalytic materials at a molecular level. The present investigation shows, a systematic study in situ about the effects of the temperature in the molecular structure of the supported phosphotungstic Wells-Dawson heteropolyacid (HPA). The infrared and Raman analyses of the samples were performed under in situ conditions from RT to 500 oC range in flowing helium. The oxide supported heteropolyacid was synthesized through a conventional impregnation method (in aqueous) at theoretical monolayer coverage. These studies provided evidences on the dehydration of the HPA upon in situ calcination. Moreover, the in situ investigation allows establishing the surface molecular structure or the thermal stability of the HPA. Additionally, the presence of crystals of HPA over TiO2 suggests that the theoretical monolayer loading should be re-evaluated.